Pricing: a Management Technology for Goat Meat Market in Bangladesh Using Simultaneous Equation Model - Yasmin, F.; Miyan, M. A. H.; Chowdhury, S. M. Z. H. (International Journal of Bio-resource and Stress Management, 2013)
This study was conducted to find out the management technology of goat meat market for improving local contribution to this market in Bangladesh. In this study a complex multi-equation system model is established to represent the management technology for goat meat market. Due to biological and economic factors interrelated with goat meat market Simultaneous Equation Model (SEM) was used by estimating Two Stage Least Square (TSLS) method. Time series data for the year 1980-2000 were used in the study. The model was analyzed using the E-views software. Results show that 1% increase in goat meat price increased the population of female adult goat, total number of goat, the supply of goat meat and income from goat by 0.003, 0.024, 0.002 and 0.309%, respectively. On the other hand, 1% increase in goat meat price reduced the demand of goat meat by 0.511%. Female adult goat, total number of goat, the supply of goat meat, income and demand are inelastic responded significantly to the price of goat meat. Due to inelasticity in demand for goat meat, producers can earn more money and it is also possible to the government for earning more money both from the national and international market. To manage the goat meat market more efficiently, pricing of goat meat as management technology can be used. For goat meat production the government should control and fix the rates such as slaughter rate of male goats and female goats, kidding rate of female goats, mortality rates of goat kids, goat meat export rate, skin export rate and live goats export rate. The price support policy should be applied/introduced not only to the price of goat meat but also for trade policy in the case of small and large scale goat farming. Therefore, ‘pricing’ of goat meat is the most important ‘management technology’ to improve and develop the goat meat market in Bangladesh.